2020
DOI: 10.14814/phy2.14386
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activation in experimental murine neonatal pulmonary hypertension

Abstract: Serotonin (5‐HT) contributes to the pathogenesis of experimental neonatal pulmonary hypertension (PH) associated with bronchopulmonary dysplasia (BPD). Platelets are the primary source of circulating 5‐HT and is released upon platelet activation. Platelet transfusions are associated with neonatal mortality and increased rates of BPD. As BPD is often complicated by PH, we tested the hypothesis that circulating platelets are activated and also increased in the lungs of neonatal mice with bleomycin‐induced PH ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…Some reports 8 elucidate that aerobic glycolysis mediates PASMCs hyperproliferation and resistance to apoptosis causing pulmonary arterial remodeling. Although other studies have confirmed that platelet is activated in both patients with PAH and murine models, 13,[35][36][37][38][39] there has been little attention towards the platelet effect on PASMCs aerobic glycolysis. Previous studies have reported that the levels of TGF-β isoforms increase and the TGF-β-dependent signaling enhances in both familial PAH and IPAH (idiopathic pulmonary arterial hypertension) patients' lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports 8 elucidate that aerobic glycolysis mediates PASMCs hyperproliferation and resistance to apoptosis causing pulmonary arterial remodeling. Although other studies have confirmed that platelet is activated in both patients with PAH and murine models, 13,[35][36][37][38][39] there has been little attention towards the platelet effect on PASMCs aerobic glycolysis. Previous studies have reported that the levels of TGF-β isoforms increase and the TGF-β-dependent signaling enhances in both familial PAH and IPAH (idiopathic pulmonary arterial hypertension) patients' lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our prior work demonstrating both increased plasma 5‐HT and pulmonary tph1 expression, as well as accumulation of platelets, the primary source of 5‐HT within the lungs of neonatal mice with bleomycin‐induced PH, we hypothesized that circulating and pulmonary 5‐HT would be increased in neonatal mice following hypoxia exposure (Davizon‐Castillo et al, 2020 ). As the majority of circulating 5‐HT is stored within platelet dense granules, we measured both platelet and platelet poor plasma 5‐HT levels.…”
Section: Resultsmentioning
confidence: 99%
“…Our lab has also demonstrated that both lung TPH1 expression and plasma 5‐HT are increased in neonatal mice with bleomycin‐induced PH and BPD (Delaney et al, 2018 ). Additionally, we have shown increased activation and accumulation of platelets, the primary source of circulating 5‐HT, in the lungs of mice with bleomycin‐induced neonatal PH (Davizon‐Castillo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 94%
“…Platelets are critical regulators of immune and inflammatory responses, and it has been hypothesised that adult (transfused) platelets are more pro-inflammatory than neonatal platelets. [5][6][7][8] In support of this hypothesis, pre-clinical studies suggest platelet transfusions trigger inflammation or dysregulated immune responses in neonates, in a context-dependent manner. 9 Whether NDI results from the direct effects of transfused platelets on the developing brain or is mediated by higher rates of IVH and BPD observed in infants randomised to the high threshold group EBNEO commentaries on manuscripts relevant to evidence-based neonatal practice are welcomed and published after a formal peer-review process.…”
mentioning
confidence: 90%
“…The mechanisms underlying increased morbidity and mortality associated with platelet transfusions are likely related to non‐hemostatic effects of platelets. Platelets are critical regulators of immune and inflammatory responses, and it has been hypothesised that adult (transfused) platelets are more pro‐inflammatory than neonatal platelets 5–8 . In support of this hypothesis, pre‐clinical studies suggest platelet transfusions trigger inflammation or dysregulated immune responses in neonates, in a context‐dependent manner 9 .…”
mentioning
confidence: 99%